Differential association of somatic and cognitive symptoms of depression and anxiety with inflammation: Findings from the Netherlands Study of Depression and Anxiety (NESDA) - Duivis, Hester E.; Vogelzangs, Nicole; Kupper, Nina; de Jonge, Peter; Penninx, Brenda W.J.H. (Psychoneuroendocrinology, 2013)
Depression and anxiety have been suggested to be associated with systemic inflammation upregulation. However, results are not always consistent, which may be due to symptom heterogeneity of depression and anxiety. There are some indications that associations with inflammation are mainly driven by somatic symptoms of depression and anxiety. We therefore set out to evaluate the differential association of somatic and cognitive symptoms of depression and anxiety with inflammation, while adjusting for demographic, health related, and lifestyle related variables. We evaluated baseline data from 2861 participants from the Netherlands Study of Depression and Anxiety (NESDA). The Inventory of Depressive Symptomatology and the Beck Anxiety Inventory were used to assess depressive symptoms and anxiety symptoms. For both scales somatic and cognitive symptoms scales were calculated. Baseline blood samples were collected to determine high sensitivity C-Reactive Protein (CRP), interleukin (IL)-6, and Tumor Necrosis Factor (TNF)-α. We used linear regression to analyze the associations adjusting for demographics and health indicators and markers for an unhealthy lifestyle. After adjustment for sociodemographic and health indicators, depressive symptoms were associated with higher levels of CRP, IL-6 and TNF-α. This association was mainly driven by somatic symptoms. For anxiety, somatic symptoms were associated with higher levels of CRP, IL-6 and TNF-α, whereas cognitive anxiety symptoms were associated with CRP (men only). Markers of an unhealthy lifestyle explained the significant associations. Especially somatic symptoms of depression and anxiety are associated with inflammation. However, this association was mostly mediated through unhealthy lifestyles among depressed and anxious individuals.